Thermodynamic property fields for xenon adsorption on various adsorbents - Lim, Jun Kai (Nanyang Technological University, 2021)
The global demand for xenon (Xe) increases significantly not only as fuel for ion thruster and ion engines but also in the electronics, lighting, and medical industry. The amount of Xe contained in Earth’s atmosphere is very low (at just 0.087 ppmv concentration). The Xe storage in the form of compressed-gas or liquified state requires massive supporting refrigeration systems, pressure reduction equipment, complex controls, and thick-walled tanks. Therefore, adsorption assisted Xe storage and separation is an alternative to the current technology. The thermodynamic property surfaces such as the enthalpy and the entropy for xenon adsorption on MIL-100(Fe), MIL-101(Cr) and UiO-66(Zr) types of metal organic frameworks (MOFs). These formulations are derived based on the rigor of classical thermodynamics by combining Gibbs law and Maxwell relations. These formulations are required in computing the isosteric heat of adsorption, specific heat capacity which enables entropy and enthalpy of the xenon-adsorbed phase into the pores of MOFs to be calculated. Employing experimentally confirmed isotherms data, the thermodynamic parameters are quantitatively calculated for temperatures ranging from 233 K to 303 K and pressures up to 100 kPa. A temperature-entropy map shows the charging and discharging processes of Xe gas in porous adsorbents under various operating conditions ranging from cryo-adsorption to ambient conditions. The entropy flow of MOFs + Xe shows a close loop during charging and discharging of Xe molecules, which indicates the confirmation of the thermal energy storage system.